2008
DOI: 10.1194/jlr.m800319-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Cardiolipin and electron transport chain abnormalities in mouse brain tumor mitochondria: lipidomic evidence supporting the Warburg theory of cancer

Abstract: Otto Warburg first proposed that cancer originated from irreversible injury to mitochondrial respiration, but the structural basis for this injury has remained elusive. Cardiolipin (CL) is a complex phospholipid found almost exclusively in the inner mitochondrial membrane and is intimately involved in maintaining mitochondrial functionality and membrane integrity. Abnormalities in CL can impair mitochondrial function and bioenergetics. We used shotgun lipidomics to analyze CL content and composition in highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
241
0
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 249 publications
(251 citation statements)
references
References 72 publications
(116 reference statements)
9
241
0
1
Order By: Relevance
“…This decline in respiratory activities is not consistent, and therefore, we hypothesized that instead of respiratory complexes' specific inhibition, this lower respiratory activity could be due to unspecific interactions of hydrophobic compounds with the mitochondrial inner membrane that could interfere with membrane fluidity (Kiebish, Han, Cheng, Chuang, & Seyfried, 2008). Indeed, swelling assay performed with Kacetate showed a slight increase in membrane permeability in the presence of P. tridentatum concentrations (250 or 500 mg.L 71 ) commonly used in traditional medicine (or to flavor rice), however these declines are not reflected in phosphorylative efficiency.…”
Section: Discussionmentioning
confidence: 95%
“…This decline in respiratory activities is not consistent, and therefore, we hypothesized that instead of respiratory complexes' specific inhibition, this lower respiratory activity could be due to unspecific interactions of hydrophobic compounds with the mitochondrial inner membrane that could interfere with membrane fluidity (Kiebish, Han, Cheng, Chuang, & Seyfried, 2008). Indeed, swelling assay performed with Kacetate showed a slight increase in membrane permeability in the presence of P. tridentatum concentrations (250 or 500 mg.L 71 ) commonly used in traditional medicine (or to flavor rice), however these declines are not reflected in phosphorylative efficiency.…”
Section: Discussionmentioning
confidence: 95%
“…Warburg averred that an irreversible injury to respiration had to occur in order to trigger the progressive striving of cells that had succeeded to engage in lactic fermentation to fulfill their energy needs, leading ultimately to the formation of a tumor (Warburg, 1956a). Mutations in mitochondrial DNA (Bonora et al, 2006), and defective mitochondrial lipid content and structure (Kiebish et al, 2008), were found to squelch respiration in some tumors, while malfunction of some Krebs cycle enzymes also contributes to apoptosis resistance and aerobic glycolysis (King et al, 2006). This suggests that mitochondrial defects may have a role in certain cancers.…”
Section: Perspectivesmentioning
confidence: 99%
“…The pellet was resuspended in HM buffer without BSA, and the protein concentration of the resuspended mitochondrial fractions was determined using the BCA protein assay (Thermo Scientifi c, Rockford, IL). disease states ( 12,13,(15)(16)(17)(18)(19). This diversity is regulated by differences in cardiolipin biosynthesis and catabolism, remodeling acyl selectivities, and transacylase as well as acyltransferase activities ( 20,21 ).…”
Section: Mitochondrial Isolationmentioning
confidence: 99%